Studi Eksperimental Performa Sepeda Motor dengan Menambahkan Torque Expansion Chamber Satu Tabung dan Dua Tabung pada Exhaust Manifold - Subroto Subroto; Sartono Putro; Pramuko Ilmu Purboputro (Creative Research in Engineering (CERIE), 2024)
This research aims to determine the effect of adding a one-tube and two-tube Torque Expansion Chamber (TEC) to the exhaust manifold on motorbike performance. Torque Expansion Chamber includes one tube with one channel and two channels, two tubes with one channel and two channels. Motorbike performance testing includes torque, power and specific fuel consumption (kbbs) using the Dyno Test. Research shows that by adding TEC, variations in the number of tubes and number of channels have an effect on better performance than standard exhaust manifolds. The best torque with the addition of one two-channel tube and two two-channel TEC. Best power with the addition of one two-channel tube and two two-channel TEC. Best fuel consumption with the addition of one tube two channel TEC.